Biopsy Versus Conservative Management of Sonographically Benign‐Appearing Solid Breast Masses in Adolescents. (1st April 2015) - Jawahar, Anugayathri; Vade, Aruna; Ward, Kathleen; Okur, Gokcan; Subbaiah, Perla
Abstract : Objectives: To determine whether the size of palpable solid breast masses in adolescents at initial sonography and their growth at follow‐up sonography could be used to decide between conservative management and tissue biopsy. Methods: This retrospective study included 37 adolescent female patients with 45 palpable benign‐appearing solid breast masses on initial sonography. They were grouped as follows: group I, masses undergoing follow‐up sonography with subsequent biopsy (n = 9); group II, masses undergoing biopsy without follow‐up sonography (n = 13); and group III, masses undergoing follow‐up sonography without biopsy (n = 23). The largest dimension, volume, volume change per month, and change in the sonographic appearance were analyzed to predict the need for biopsy. A combination of a largest dimension greater than 3 cm and volume change per month greater than 16% was used to assess the need for biopsy. Sonograms of 22 masses were correlated with histopathologic diagnoses. Results: None of the masses that underwent follow‐up sonography showed changes in their sonographic appearance. All masses that underwent biopsy were benign on histopathologic analysis. There was no significant difference in the largest dimension among the groups at initial sonography or between groups I and III at follow‐up sonography. The volume change was smaller for fibroadenomas (n = 7; mean, 22.67%) than benign phyllodes tumors (n = 2; mean, 45.30%) in group I, but the difference was not significant ( P = .384). However, the volume change for groups I and III showed a significant difference ( P = .026). Neither size greater than 3 cm nor volume change greater than 16% predicted pathologic outcomes. Conclusions: If the combined criteria for assessing benignity of palpable breast masses had been used, biopsy could have been reduced by 89% in group I and deemed not necessary in 96% of group III breast masses.